Penerapan Manajemen Bandwidth Menggunakan Teknik Load Balancing Dengan Meotode NTH Berbasis MikroTik - Athiya Alif Gunawan; Yudi Sutanto (Unit Penelitian, Pengabdian Kepada Masyarakat dan Penjamnan Mutu Akademi Komunitas Negeri Pacitan, 2026)
With the rapid development of the internet as a means of communication and information, organizations and businesses are required to ensure optimal network availability and performance. One common approach is to use multiple ISPs to improve internet connection reliability. This study describes the application of load balancing techniques in bandwidth management using the NTH method with two MikroTik-based ISPs. The NTH method allows traffic load to be distributed based on the number of sessions or packets, providing flexibility in managing and distributing network traffic. The purpose of this study is to analyze the effect of applying load balancing techniques using the NTH method on bandwidth management efficiency and internet availability. Through data collection and analysis, optimization of resource utilization, it is hoped that insights can be gained on improving network performance, optimizing resource utilization, and potential benefits for many dual ISP users. It is hoped that the results of this study can contribute to a better understanding of the application of load balancing techniques, particularly using the NTH scheme in the context of bandwidth management on MikroTik-based dual ISPs. The conclusions and recommendations from this study provide a basis for organizations and businesses to optimize their network infrastructure, improve bandwidth usage efficiency, and ultimately enhance the user experience when accessing internet services.